Association of adiposity and fitness with triglyceride-to-high-density lipoprotein cholesterol ratio in youth - Danladi Ibrahim Musa; Abel Lamina Toriola; Nurudeen O Abubakar; Sunday Omachi; Victor B Olowoleni; Kolade B Ayodele (Wolters Kluwer Medknow Publications, 2023)
Background : The ratio of triglycerides-to-high-density lipoprotein cholesterol (TG/HDL-C) is considered a robust biomarker of metabolic syndrome (MetS) and is associated with several diseases, including type 2 diabetes mellitus (T2DM) and hypertension (HTN). This study examined the independent association of adiposity and fitness with the TG/HDL-C ratio. Materials and Methods : This is a cross-sectional study comprising 403 (201 girls) Nigerian adolescents aged 11-19 years. Participants were evaluated for body mass index, cardiorespiratory fitness, and TG/HDL-C. Regression models adjusting for age and biological maturity were used to evaluate the association of adiposity and fitness with TG/HDL-C ratio. The TG/HDL-C ratios of 1.0 mmol/L and 1.1 mmol/L were used to stratify female and male participants into low- and high-risk groups, respectively. Results : Of the 135 high-risk adolescents, 21.1%, 5.5%, 12.7%, 14.9%, and 0.5% were at risk of T2DM, systolic HTN, diastolic HTN, abdominal obesity, and MetS, respectively. The independent variables were significantly associated with TG/HDL-C ratio only in boys but not girls. In boys, high adiposity (β = 0.193; P = 0.025) and low fitness (β = -0.169; P = 0.048) were independently associated with the dependent variable. Unfit boys were 3.9 (95% confidence interval [CI] =1.37-10.94, P = 0.011) times more likely to develop elevated TG/HDL-C ratio than their fit peers. The likelihood of girls at risk of MetS developing a high TG/HDL-C ratio was 13.7 (95% CI = 3.89-48.32, P < 0.001) times compared to their counterparts without MetS. Conclusions : Adiposity and fitness were independently associated with TG/HDL-C in boys but not in girls. Health promotion intervention focusing on lowering TG/HDL-C ratio among Nigerian adolescents should include an emphasis on healthy diet and endurance activity programs.